Economic-Geographic Analysis of Differentiated Development in Croatian Coastal Region - Braičić, Zdenko; Lončar, Jelena (Journal for Geography, 2015)
The main characteristic of the current development process in Republic of Croatia's coastal area is its unevenness. While former studies on differences in regional development have mainly discussed inequalities in terms of coast/inland/islands, this study analyzes a differentiated economic development along the Croatian coast, not including the islands. Basic analytical spatial units are cities and municipalities that can be classified into seven major coastal spatial units (sub-regions): Istria, Rijeka, Sub-Velebit, Zadar, Šibenik, Split and Dubrovnik-Neretva coastal area. In order to rate the level of development and determine differences in economic activities of coastal spatial region, several economic indicators have been taken into account. The results have confirmed that Istria and Rijeka coastal subregions are the most prosperous parts of Croatian coast. The economic orientation of cities and municipalities on the coast has been determined with the index of specialization.
Keywords: coastal spatial units; economic development; indicators; functional specialization; Croatia